Draft Five Year Plan 1978-83 E. S. I. Government of Madhya Pradesh - Planning Commission (Planning Commission, 1978)
Employees State Insurance Scheme is a Social Security Scheme under the Central Government E.S.I. Act 1943. As per agreement between the E.S.I Corporation and the State Government 7/8th share of overall expenditure subject to ceiling on medical care is borne by the E.S.I Corporation and 1/8th share is to be borne by the State Government. the E.S.I Corporation bears the whole expenditure on the construction of E.S.I Hospitals/State Insurance Dispensaries and staff quarters in Madhya Pradesh.
Government of Madhya Pradesh